3(f+7)+9=13+5f

Simple and best practice solution for 3(f+7)+9=13+5f equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(f+7)+9=13+5f equation:


Simplifying
3(f + 7) + 9 = 13 + 5f

Reorder the terms:
3(7 + f) + 9 = 13 + 5f
(7 * 3 + f * 3) + 9 = 13 + 5f
(21 + 3f) + 9 = 13 + 5f

Reorder the terms:
21 + 9 + 3f = 13 + 5f

Combine like terms: 21 + 9 = 30
30 + 3f = 13 + 5f

Solving
30 + 3f = 13 + 5f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-5f' to each side of the equation.
30 + 3f + -5f = 13 + 5f + -5f

Combine like terms: 3f + -5f = -2f
30 + -2f = 13 + 5f + -5f

Combine like terms: 5f + -5f = 0
30 + -2f = 13 + 0
30 + -2f = 13

Add '-30' to each side of the equation.
30 + -30 + -2f = 13 + -30

Combine like terms: 30 + -30 = 0
0 + -2f = 13 + -30
-2f = 13 + -30

Combine like terms: 13 + -30 = -17
-2f = -17

Divide each side by '-2'.
f = 8.5

Simplifying
f = 8.5

See similar equations:

| y=1/3x+4/3 | | 25y-3=-10y+6 | | (1/2)a-4=3-(1/4)a | | 4x-4-3= | | 6x+2.0=3x-3/6 | | 11x+6=6x+27 | | X-3+X+((X-3)*3)=38 | | (49/7)+3=100/50 | | y=(1/2)x-18 | | -5.1x+4.1=6.7x-1.8 | | 3(-6x)= | | 4x-4/8-3=5 | | Z^2(2z-1)=0 | | 13-7x=94-28x | | (49/7)+3=100/10 | | 5q+11=26 | | (49/7)+3=100/3 | | 50t+6=-7 | | 5t-a=8t | | (49/7)+3=100/7 | | (49/7)+3=100/ | | 5(x+9)-2x=18 | | 2y=-7+3 | | 7y+9=4y | | 4(6)+3y=18 | | lnx=-7 | | X^4=8x^2+20 | | 16x+1+25=122 | | b(13b+5)=8 | | x+4-6=2x-6 | | 16x+26=122 | | 8x=9x-5/2 |

Equations solver categories